Total Quality Management (TQM) in Islamic Education: A Qur’anic Perspective - Mucharobin, Mucharobin (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
Islamic education in the midst of global competition is required to adapt to the ever-changing circumstances and conditions of the times. Traditional organizational management will cause Islamic education to lose its direction and existence. This study aims to conduct a review and analysis of the principles of Total Quality Management (TQM) in Islamic education from the perspective of the Qur'an. The method used in this study is a literature review, involving the examination of various relevant and related sources, including books and scientific journals. The analysis involves comparing and integrating the principles of TQM from the perspective of the Qur'an. The results of the study indicate that the main principles of TQM are consistent with and have points of convergence with the teachings of the Qur'an. For example, the principle of “layyinah” is in line with the principle of customer satisfaction, the principle of ‘syawir’ is consistent with the principle of fact-based management, while the principle of respect for all people is in line with the principle of “tahiyyat” as explicitly mentioned in the Qur'an. Similarly, continuous improvement in quality enhancement efforts is relevant to the Quran. This study recommends the importance of adopting TQM as a management approach for Islamic education that aligns with the values of the Quran.